Africa’s Transition from Fossil Fuels to Renewable Energy Toward the Circular Economy - Bui, Tu Ngoc (Asian Journal of Science, Technology, Engineering, and Art, 2024)
The term "circular economy" has gained popularity over the past decade, particularly in sustainability, resource management, and productivity. Increasingly, both public and private organizations are exploring its application in daily operations. This article reviews the literature on Africa's energy transition and whether it can be guided by circular economy principles. The study finds that Africa's energy demand will rise significantly due to industrialization and population growth. While Sub-Saharan Africa relies mainly on renewable energy, countries like Algeria, Nigeria, Morocco, South Africa, and Egypt still depend heavily on fossil fuels. Researchers suggest that a circular economy approach could promote renewable energy adoption. However, more research is needed to explore the potential of circular principles in supporting the energy transition.